Can Match-Mimicking Intermittent Practice Be Used as a Simulatory Training Mode of Competition Using Olympic Time Frame in Elite Taekwondo Athletes? - Sheng-Ju Chuang; Yu-Chi Sung; Chung-Yu Chen; Yi-Hung Liao; Chun-Chung Chou (Frontiers in Physiology, 2019)
Aim: The physiological realities between Taekwondo (TKD) simulation kicking training and TKD competition according to the Olympic time frame remain unclear. The purpose of this study is to establish an Olympic match-simulated kicking model and compare its effects with real TKD competition on physiological challenges and hormonal responses during serial matches in elite athletes.Method: Sixteen elite TKD athletes randomly were assigned into either a TKD match-simulated kicking group (TMSK; N = 8, age: 21.3 ± 0.2 years) or a simulated TKD competition group (STC; N = 8, age: 21.6 ± 0.5 years). Both groups performed either simulated kicking or TKD competitions in the same time-course order, and all physiological parameters and blood sampling time-points were identical between groups. The heart rate (HR) and rating of perceived exertion (RPE) were recorded during each match-simulated kicking and TKD competition session. Blood samples were obtained before competition (Pre-Comp.), after competition—in ths case meaning four consecutive matches (End-Comp.), and 24 h after the first match (Next day) for determination of biomarkers of muscle damage (myoglobin and CK), hematological profiles, and hormonal profiles (testosterone and cortisol).Results: The responses of HR, RPE, and blood lactate levels during the consecutive testing sessions showed no differences between TMSK and STC. The changes in CK and myoglobin were greater in STC (p < 0.05), and a greater decrease in red blood cell (RBC) loss was observed in the STC group (p < 0.05). Compared with TMSK, the inflammatory state, reflected by the ratios of neutrophils-to-lymphocyte (NLR) and platelets-to-lymphocyte (PLR), was higher in STC (p < 0.05). Moreover, the catabolic state (cortisol/testosterone) was greater in STC than in TMSK (p < 0.05).Conclusion: We demonstrated that, compared with TMSK, the STC produced greater muscle damage, inflammatory responses, and catabolic stress in the Olympic competition time frame in elite male TKD athletes. Although TMSK is capable of eliciting similar physiological challenges as TKD competition, the muscle damage and hormonal profiles provoked by TMSK were not comparable to TKD competition. Our findings provide science-based data and better understanding for coaches, athletes, and sports scientists to develop TKD-specific training programs for Olympic preparation.